INDIGENOUS COMMUNICATION SYSTEMS AS DETERMINANTS OF CULTURAL RESURGENCE IN YORUBA SOCIETIES OF OYO AND OSUN STATES, NIGERIA (2013)
Indigenous Communication System (ICS) has been identified as an indispensable cultural tool for strengthening ties between elders and youths that can lead to effective promotion and transition of cultural heritage from one generation to the other. Despite the relevancy of ICS into African cultural heritage, previous studies have consentrated more on the importance of modern communication system in Yoruba communities than the ICS. This study, therefore, investigated the influence of indigenous communication system (ideographics, proverbs, folk stories, ‘aroko’ system and folk music) on cultural resurgence in Yoruba communities of Oyo and Osun States, Nigeria. The survey research design was adopted. The stratified random sampling technique was used to select 1,204 respondents comprising: 671 males and 533 females from 12 purposively selected Yoruba indigenous communities in six towns in Oyo state (Aaje, Olugbode, Alapinni, Sakutu, Oje and Babasale) and Osun States (Lagere, Iremo, Okegada, Isale Oja, Isale Osun and Ailie). Two instruments were used: Indigenous Communication System Scale (r=0.79) and Cultural Resurgence Questionnaire (r=0.92). These were complemented with 12 sessions of Focus Group Discussions (FGDs) with adult inhabitants; one each in the 12 selected communities. Four research questions were answered and two hypotheses tested at 0.05 level of significance. Data were subjected to percentages, chi-square, Pearson Product Moment correlation and content analysis. Indigenous communication systems significantly influenced cultural resurgence in Yoruba communities (x2=628.00, P<0.05). They correlated with cultural resurgence as follows: folk music (r=0.04), folk stories (r=0.36), proverbs (r=0.28), ‘aroko’ system (r=0.22); while ideograph did not. This shows that cultural resulgency in Yoruba communities is more associated with folk music, folk stories, proverbs and ‘aroko’ system. Folk music (42.0%), folk stories (31.0%) and proverbs (27.0%) serve as the prominent outlets, vehicles and media of Yoruba thoughts, feelings, emotions and ideas which give expression to culture. Adoption and usage of ICS correlated with age (r=0.79) and nature of occupation (r=0.56). Indigenous Communication Systems were mostly common among older males. Despite its importance, ICS were deeply enshrined in coding, symbols, abstract forms, spiritualities, secret and hence the difficulties in their understanding, interpretations and sustainability. This led to the negative attitudes and apathy towards them particularly among emerging generations. Besides, there was evidence of neglects of communal living, spirit of brotherliness and family-ties. Folk music, folk stories, proverbs, and ‘aroko’ system forms of indigenous communication system positively enhanced cultural resurgence in Yoruba communities. However, in order to ensure better understanding, easy interpretation and effective sustainability of Yoruba culture, there is the need to simplify the decoding and interpretations of most of the indigenous communication systems. Yoruba folk music and stories should be encouraged and promoted more among the younger generation. Particularly its use and interpretions must be popularised through the modern media.